Mechanical Properties of Tunnel Muck with Fly-Ash Geopolymer - Dong Yang; Zhiqin Xi; Qiang Chen; Shuisheng Li (Advances in Civil Engineering)
The tunnel muck has a great potential to be used as a recyclable engineering material in transit and other civil work projects instead of being deposited as construction waste. In this work, the geopolymer is generated by alkali-activated fly ashes, which act as cementitious materials to strengthen the tunnel muck. The tunnel muck has to be dehydrated, grinded, and screened before being treated by alkali-activated fly ash. The effect of the mass ratio between fly ash and tunnel muck (Mfa/Mtm), the mass ratio between Na2SiO3 solution and NaOH solution (MNa2SiO3/MNaOH), the ratio between liquid and solid (Mliquid/Msolid), and molarity of NaOH on the strength of geopolymer were systematically studied by conducting the uniaxial compression experiments. The experimental results indicate that the liquid-to-solid ratio is the most important parameter to the geopolymer strength after the alkali-activated fly ash treatment. On the contrary, molarity of NaOH is less effective on the geopolymer strength. Moreover, the optimum scheme is concluded according to the experimental results as follows: the mass ratio between tunnel muck and fly ash, the mass ratio between Na2SiO3 solution and NaOH solution, the ratio between liquid and solid, and molarity of NaOH are 1 : 2, 1.8, 0.18, and 10 mol/L, respectively. Meanwhile, the SEM images indicate that flocculence from the active substance in fly ash is a crucial component as the cementing material.